Papulosquamous: clinicopathological - Narayankar, Shilpa Laxmikant; Pandit, Gopal Ambadasrao (International Journal of Research in Medical Sciences, 2017)
Background: Papulosquamous disorders comprise a group of dermatoses that have distinct morphologic features. The characteristic primary lesion of these disorders is a papule, usually erythematous, that has a variable amount of scaling on the surface. Some common papulosquamous dermatoses are Psoriasis, Pityriasis rosea, Lichen planus, Seborrheic dermatitis, Pityriasis rubra pilaris and Parapsoriasis. Drug eruptions, tinea corporis, and secondary syphilis may also have papulosquamous morphology. Because all papulosquamous disorders are characterized by scaling papules, clinical confusion may result during their diagnosis. Methods: The present study of 60 cases of papulosquamous disorders of the skin was carried out in the Department of Pathology of a tertiary care centre from December 2009 to October 2011. In this study, the patients which were clinically diagnosed as papulosquamous disorders of skin, before starting the treatment and attending the outdoor skin department were selected. Histopathological findings were interpreted in light of clinical details. Results: An analysis of the clinical diagnosis with the histopathological diagnosis of papulosquamous disorders of the skin, revealed a positive correlation in 54 (90%) cases and a negative correlation in 6 (10%) cases. Conclusions: Histopathology may not resolve the issue and the picture is more typically ‘compatible with’ rather than ‘diagnostic of’ a clinical diagnosis. In these circumstances an attempt at clinicohistopathological correlation serves as an ideal approach.